2011
DOI: 10.1002/term.492
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of chitosan-gelatin scaffolds for dermal tissue engineering

Abstract: Porous scaffolds for dermal tissue engineering were fabricated by freeze-drying a mixture of chitosan and gelatin (CG) solutions. Different crosslinking agents including glutaraldehyde, 1-(3-dimethylaminopropyl)-3-ethyl-carbodimide hydrochloride (EDC), and genipin were used to crosslink the scaffolds and improve their biostability. The porous structure and mechanical properties were determined for the scaffolds. The proliferation of human fibroblasts in the scaffolds was analyzed. It was found that EDC crossli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 40 publications
4
46
0
1
Order By: Relevance
“…The enhancement varied with the ratio of chitosan to gelatin; the optimum C:G ratio ranged from 2:5 to 4:5. This result was similar to that of previous studies, where the C:G ratio in this range was found to be optimal for cellular adhesion in chitosan-gelatin based materials [26,[39][40][41]. Although not fully understood, the ratio of chitosan to gelatin can affect a number of characteristic of the scaffolds, which could directly or indirectly influence the adhesion of cells, as well as their proliferation and arrangement on the substrate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The enhancement varied with the ratio of chitosan to gelatin; the optimum C:G ratio ranged from 2:5 to 4:5. This result was similar to that of previous studies, where the C:G ratio in this range was found to be optimal for cellular adhesion in chitosan-gelatin based materials [26,[39][40][41]. Although not fully understood, the ratio of chitosan to gelatin can affect a number of characteristic of the scaffolds, which could directly or indirectly influence the adhesion of cells, as well as their proliferation and arrangement on the substrate.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the ratio of chitosan and gelatin, the concentration of the constituents is also known to affect the biological properties of scaffolds [39]. Differences in cell adhesion (at day 1) were not observed over a range of concentrations from 1% to 3%.…”
Section: Discussionmentioning
confidence: 67%
“…For instance, freeze-drying is a common approach for preparing gelatin scaffolds; [44][45][46] however, this technique does not allow for control over the pore dimensions. An electrospinning approach [47,48] is also widely used for preparing …”
Section: Scaffolds Fabricated Via Three-dimensional Plottingmentioning
confidence: 99%
“…A higher absorbance value of the hemoglobin solution indicates a slower clotting rate. As presented from the results, both CNMs and gelatin show a better hemostatic effect than that of SMPU and gauze within 15 min, which can be attributed to the following two possible reasons: (1) gelatin and chitosan are hydrophilic and belong to ionic species which can induce the platelet coagulation through electrostatic adsorption interactions [49]; (2) nanofibrous mats have larger large specific surface area than that of gauze.…”
Section: Hemostatic Performancementioning
confidence: 92%